Application of Rainwater Harvesting Technology to Supply Sustainable Domestic Water - Joleha; Mulyadi, Aras; Wawan; Suprayogi, Imam (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2019)
Rainwater harvesting that is good and right by the needs of household clean water is one of the problems for the people in the islands in Indonesia, especially Merbau Island which is located in the Kepulauan Meranti Regency, Riau Province. The only source of clean water that can be enjoyed easily and cheaply is rainwater. Rainfall on Merbau Island ranges between 2.000 – 4.000 mm per year which is classified as moderate. A survey of 100 randomly selected people was conducted, with a questionnaire containing components for rainwater harvesting (RWH) and other core questions. If available rainfall is used optimally, the need for clean water on the island can be met. Calculation of rainwater for cooking, drinking and washing needs is estimated to be around 15 lpcd. The data obtained is rainfall in 2016 with a total rainfall of 1,754 mm, roof storage area of 36 m2, and the type of roof used is zinc. Rain cycle V2 simulation produces a 3 m3 volume rainwater storage tank, with a construction cost of Rp. 10,365,000. This tank can meet the needs of clean water for five family members for a year.